PERMASALAHAN PENGGUNAAN BAHASA INDONESIA YANG BAIK DAN BENAR DI MEDIA SOSIAL DALAM UPAYA PELESTARIAN BAHASA NASIONAL - Aprilia; Calista Apria; Epi Fania Weli; Gusti Yani; Saptiana Sulastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the problem of using proper and correct Indonesian on social media in an effort to preserve the national language. The method used is a qualitative descriptive approach with observation and documentation techniques of posts on Facebook, Instagram, and TikTok. The results show that language use on social media is still dominated by non-standard forms, abbreviations, and the mixing of foreign languages ​​that do not comply with linguistic rules. This phenomenon is influenced by factors of communication practicality, digital culture, and low language awareness. Consequently, formal Indonesian language skills have the potential to decline if not addressed immediately. Therefore, efforts are needed to increase linguistic literacy and public awareness in using proper and correct Indonesian in the digital space as part of preserving national identity.